PARTISIPASI MASYARAKAT DALAM KEGIATAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI DI KELURAHAN RANOMUUT KECAMATAN PAAL 2 KOTA MANADO (Community Participation in Mandiri Community Empowerment National Program (PNPM Mandiri) Activities in Kelurahan Ranomuut Paal 2 Sub District, Manado City) - Wendianus Wenda; Benu Olfie L. S.; Vicky R. B. Moniaga (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The objective of this research is to see how Community Participation in Mandiri Community Empowerment National Program Activities in Kelurahan Ranomuut Paal 2 Sub District, Manado City. This research takes place for 3 months from October to December 2017. The research site is in Kelurahan Ranomuut, Paal 2 Sub-District Manado City. Data collection techniques carried out in this study were interview techniques. Sample selection using the method intentionally (purposive sampling). The number of respondents is 10 people who are members of the group. Data analysis techniques used in this study are descriptive analysis techniques presented in table form. The research resultsÂ showed that the Urban Independent Program in Kelurahan Ranomuut, Paal Dua Sub District, Manado City based on Community Participation in the Implementation Planning and Evaluation stage belongs to the active category.Keywords:Â Community Participation, PNPM Mandiri